Logic-based benders decomposition algorithm for contamination detection problem in water networks - Hooshmand, F.; Amerehi, F.; MirHassani, S.A. (Computers & operations research, 2020)
•Sensor location problem on water distribution network under budget limitation is studied.•The aim is to maximize the ability of identifying the source of contamination.•A bi-objective MILP with a predefined order on the objective functions is presented.•By utilizing the problem structure, a logic-based benders decomposition algorithm is presented.•Computational results over large-sized networks confirm the efficiency of the proposed algorithm. To prevent the serious hazards caused by the intrusion of contaminants into the water distribution network, equipping the network with monitoring sensors is necessary. In this regard, the identification criterion is an important and recently addressed issue indicating that the sensors should be located so that in the case of intrusion of contamination, not only at least one sensor responds, but also it is possible to identify the source of contamination intrusion, as well. This paper addresses the sensor location problem with the identification criterion assuming that a limited budget is available for the sensor placement, and the aim is to minimize the number of vulnerable nodes having the same alarm pattern. First, the problem is formulated as a bi-objective mixed-integer linear programming model, assuming that the objective functions are ordered based on a given prioritization. Then, by utilizing the underlying problem structure, an exact logic-based Benders decomposition algorithm is presented. Computational results over moderate and large-sized instances confirm the efficiency of the proposed algorithm.